2022
DOI: 10.3329/jujbs.v10i1-2.60850
|View full text |Cite
|
Sign up to set email alerts
|

First report of pre-harvest amla fruit rots disease caused by Pestalotiopsis sp. in Bangladesh

Abstract: Fruit rot disease of Amla (Phyllanthus emblica L.) reduces the quality of the fruits and causes economic loss. An investigation was conducted to find out pre-harvest fruit rot fungal pathogen associated with Amla fruits. The fungal pathogen was isolated using tissue planting method. Both morphological and molecular characterization confirmed the pathogen identity as Pestalotiopsis sp. Result indicated that Pestalotiopsis sp. showed the highest radial mycelial growth on potato dextrose agar (PDA) medium. The ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, it affects mainly the leaves, causing leaf spot (De Jesus et al., 2022 ; Herliyana et al., 2022 ; Shen et al., 2014 ; Yuan et al., 2022 ) and leaf blight (Bhuiyan et al., 2022 ; Herliyana et al., 2022 ; Jeon et al., 2007 ; Jeon & Cheon, 2014 ; Ngobisa et al., 2018 ; Wu et al., 2009 ; Xiao et al., 2016 ; Zhong Jiu et al., 2010 ). It can affect roots, causing root rot (Lu et al., 2016 ), but also fruits, causing fruit spots (Chuanqing et al., 2010 ; Shi et al., 2015 ), scabby fruit canker (Keith et al., 2006 ) and pre‐ (Sultana et al., 2021 ) and post‐harvest fruit rot (Chen, Chen, et al., 2016 ; Li et al., 2016 ), and to a lesser extent twigs, causing twig blight (Ren et al., 2021 ). Nevertheless, disease symptoms caused by P. microspora are similar to those caused by other Pestalotiopsis species or other fungal genera, which makes the detection of P. microspora based merely on symptoms unlikely.…”
Section: Pest Categorisationmentioning
confidence: 99%
“…However, it affects mainly the leaves, causing leaf spot (De Jesus et al., 2022 ; Herliyana et al., 2022 ; Shen et al., 2014 ; Yuan et al., 2022 ) and leaf blight (Bhuiyan et al., 2022 ; Herliyana et al., 2022 ; Jeon et al., 2007 ; Jeon & Cheon, 2014 ; Ngobisa et al., 2018 ; Wu et al., 2009 ; Xiao et al., 2016 ; Zhong Jiu et al., 2010 ). It can affect roots, causing root rot (Lu et al., 2016 ), but also fruits, causing fruit spots (Chuanqing et al., 2010 ; Shi et al., 2015 ), scabby fruit canker (Keith et al., 2006 ) and pre‐ (Sultana et al., 2021 ) and post‐harvest fruit rot (Chen, Chen, et al., 2016 ; Li et al., 2016 ), and to a lesser extent twigs, causing twig blight (Ren et al., 2021 ). Nevertheless, disease symptoms caused by P. microspora are similar to those caused by other Pestalotiopsis species or other fungal genera, which makes the detection of P. microspora based merely on symptoms unlikely.…”
Section: Pest Categorisationmentioning
confidence: 99%
“…Fungi cause rot, blue mold, and green mold diseases in Amla fruits [6]. Pestalotiopsis is well known as a pre-harvest pathogen, which is responsible for Amla fruit rot disease; also, fruit spot diseases caused by Thielaviopsis paradoxa were reported in Bangladesh [6,7]. Sengupta et al [8] reported post-harvest diseases of Amla like blue mold; anthracnose and fruit rot and suggested its possible management strategies including physical, chemical, and biological methods.…”
Section: Introductionmentioning
confidence: 99%